Precipitation Data - M. Knapp (Kansas Agricultural Experiment Station Research Reports, 2016)
Precipitation data for agricultural experiment stations in Kansas, 2014-2015.
Keywords: Weather; Precipitation; Fertilizer weather; Fertilizer precipitation